Pré baby: o lúdico como indutor no ensino da dança para crianças de 2 e 3 anos - FERREIRA, Jéssica Raisa Azevedo (2021)
The present research aimed to analyze the teaching methodologies of dance developed in my daily activities as a teacher of classical ballet with children of 2 and 3 years old - pre baby group of the School of Dance Art in Movements. It was a qualitative study focused on the autobiographical research, having as an analysis instrument the lesson plans for the first semester of 2019. The results of the study showed that the dance provides the extension of the physical, psychological, motor and even language aspects of child. The dance classes when developed having the games, toys and games as a methodological resource can contribute to an affective memory of dancing teachers and students.